Integrating Dynamic Capabilities and Social Capital: Enhancing Competitiveness in Tourism Industry - Yuwono, Matias Andika; Ellitan, Lena (CV. Ulil Albab Corp, 2024)
Integrating dynamic capabilities and social capital in tourism companies' marketing and operational management is crucial to achieving competitive advantage and providing added value to customers. From the analysis of the seven articles studied, there are similarities in recognizing the importance of adapting to market and business environment changes and managing strong relationships with suppliers, business partners and local communities. However, there are differences in the focus and approach of each article, ranging from an emphasis on managing costs and risks in the supply chain to applying technology to improve operational efficiency. The new idea proposed from this analysis is the importance of strengthening the flow of information and skills between dynamic capabilities and social capital so that companies can combine valuable market knowledge with the ability to innovate and adapt to market changes. By building solid relationships with suppliers, business partners, and local communities, companies can strengthen their brand image, increase external collaboration, and increase customer satisfaction. Tourism companies can achieve long-term sustainability through this integrated approach in an increasingly dynamic and competitive business era.